If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + w)(4w + 3) = 0 Reorder the terms: (7 + w)(3 + 4w) = 0 Multiply (7 + w) * (3 + 4w) (7(3 + 4w) + w(3 + 4w)) = 0 ((3 * 7 + 4w * 7) + w(3 + 4w)) = 0 ((21 + 28w) + w(3 + 4w)) = 0 (21 + 28w + (3 * w + 4w * w)) = 0 (21 + 28w + (3w + 4w2)) = 0 Combine like terms: 28w + 3w = 31w (21 + 31w + 4w2) = 0 Solving 21 + 31w + 4w2 = 0 Solving for variable 'w'. Factor a trinomial. (7 + w)(3 + 4w) = 0Subproblem 1
Set the factor '(7 + w)' equal to zero and attempt to solve: Simplifying 7 + w = 0 Solving 7 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + w = 0 + -7 w = 0 + -7 Combine like terms: 0 + -7 = -7 w = -7 Simplifying w = -7Subproblem 2
Set the factor '(3 + 4w)' equal to zero and attempt to solve: Simplifying 3 + 4w = 0 Solving 3 + 4w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4w = 0 + -3 4w = 0 + -3 Combine like terms: 0 + -3 = -3 4w = -3 Divide each side by '4'. w = -0.75 Simplifying w = -0.75Solution
w = {-7, -0.75}
| 108=3x*2x | | 4a+6b=1200 | | 3x^2-2x-17=-1 | | 51-10z=23 | | 8x+4y=20z | | 5x-3(x-5)=-8+5x+5 | | (3x^4y^2)(5xy^10)= | | 4x+5y=376 | | 7m^2-12m+1=0 | | .37=.7x+.3y | | .05(2n-10)=22 | | 6+9(1-2n)=-10+7(5n-4) | | 3x+10=-14-3x | | 7x-9=-3x-99 | | 3F+1B=6F | | 10x=3x-21 | | -6+7x-8-9x= | | Y=3x^2-18x+24 | | 5x-7=10x+2 | | 7(x-1)(x+1)=0 | | 3x+1=7x+45 | | -8m+2-2(m-1)=4m-(9m-3)-7m+5 | | (2y+9)(4-y)=0 | | 4(8y-7)=18-9y | | 6(x-9)=3-(x+45) | | x*4+y*5=376 | | -2(k+4)-k-2=-3(k+5)+5 | | 3x+9=-4x-54 | | -5(x-6)-7=23 | | 0x+0y+0z=5 | | 3x*25=68 | | x+(x*0.4)=64898.97 |